Appropriate age range for introduction of complementary feeding into an infant's diet. (12th September 2019) - ; Castenmiller, Jacqueline; de Henauw, Stefaan; Hirsch‐Ernst, Karen‐Ildico; Kearney, John; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; Pentieva, Kristina; et al.
Abstract: Following a request from the European Commission, the Panel on Nutrition, Novel Foods and Food Allergens (NDA) revised its 2009 Opinion on the appropriate age for introduction of complementary feeding of infants. This age has been evaluated considering the effects on health outcomes, nutritional aspects and infant development, and depends on the individual's characteristics and development. As long as foods have an age‐appropriate texture, are nutritionally appropriate and prepared following good hygiene practices, there is no convincing evidence that at any age investigated in the included studies (< 1 to < 6 months), the introduction of complementary foods (CFs) is associated with adverse health effects or benefits (except for infants at risk of iron depletion). For nutritional reasons, the majority of infants need CFs from around 6 months of age. Infants at risk of iron depletion (exclusively breastfed infants born to mothers with low iron status, or with early umbilical cord clamping (< 1 min after birth), or born preterm, or born small‐for‐gestational age or with high growth velocity) may benefit from earlier introduction of CFs that are a source of iron. The earliest developmental skills relevant for consuming pureed CFs can be observed between 3 and 4 months of age. Skills for consuming finger foods can be observed in some infants at 4 months, but more commonly at 5–7 months. The fact that an infant may be ready from a neurodevelopmental perspective to progress to a more diversified diet before 6 months of age does not imply that there is a need to introduce CFs. There is no reason to postpone the introduction of potentially allergenic foods (egg, cereals, fish and peanut) to a later age than that of other CFs as far as the risk of developing atopic diseases is concerned. Regarding the risk of coeliac disease, gluten can be introduced with other CFs. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2019.EN-1686/full This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2017.4969/full